Proceso de cobranza del comisariato “D-Fasil” - Naranjo Piguave, Denny Maibeht (2019)
The Commissariat "D-Fasil" is located in Mata de Cacao Av. Los Rios s / n and Peatonal, is a small private sector company, and is categorized into being obliged to keep accounts, with a single taxpayer record # 1202986590001, its ordinary business turn corresponds to the wholesale and retail purchase and sale of mass consumer products, hardware and bazaar, this entity was chosen to carry out the present case study which has as its theme "COMMISSARIATE COLLECTION PROCESS D- FASIL. "